Metabolite Profiling and Bioactivity Assessment of Antioxidant and Antibacterial Properties in Bulb Fractions of Eleutherine bulbosa (Mill.) Urb - Nurma Angeliani Komalasari; Natalia Natalia Marbun; Gustini Syahbirin; Laksmi Ambarsari; Purwatiningsih Sugita (Tropical Biopharmaca Research Center, IPB University, 2026)
Eleutherine bulbosa is known to contain diverse secondary metabolites with pharmacological potential. This study aimed to identify the bioactive compounds in the ethanol, n-hexane, and unsaponified n-hexane fractions of E. bulbosa bulbs and evaluate their antioxidant and antibacterial activities. The bulbs were extracted using ethanol, followed by n-hexane fractionation and saponification. Antioxidant activity was determined using the DPPH assay, and antibacterial activity was assessed against Staphylococcus aureus and Escherichia coli using the disc diffusion method. LC-MS/MS and GC-MS analyses identified compounds such as eleutherol, resveratrol, coniferaldehyde, and stigmasterol. The ethanol fraction exhibited the highest antioxidant activity (IC₅₀ = 47.54 ± 0.03 mg/L), while the unsaponified n-hexane fraction showed the strongest antibacterial effect (inhibition zone = 16.12 ± 0.16 mm). These findings confirm the potential of E. bulbosaas a natural source of antioxidant and antibacterial agents.